Modification of Vermiculite with Ionic Liquids - CUI, WEN-FENG; GAO, XIANG-HU; WANG, YUN-PU (Asian Journal of Chemistry, 2010)
Vermiculite, a layered silicate, was modified with three different ionic liquids i.e., 1-ethyl-3-methyl imidazolium tetrafluoroborate, 1-butyl- 3-methyl imidazolium tetrafluoroborate and methyl-1-methylimidazolium- 3-acetate tetrafluoroborate. The modified vermiculite was characterized by SEM, FTIR, WXRD and TGA. The data shows an overall increase in interlamellar spacing as a result of sodium cation exchange with the imidazolium cations and improved thermal stability vs. commercial layered silicates modified with long chain quaternary ammonium salts. Data is also reported on the evaluation of the modified clays in the preparation of composite polymer membranes.